Data triangulation in the context of opioids monitoring via wastewater analyses. (1st June 2015) - Been, Frederic; Benaglia, Lisa; Lucia, Sonia; Gervasoni, Jean-Pierre; Esseiva, Pierre; Delémont, Olivier
Highlights: Sampling strategy reliability assessed via methadone (wastewater and prescription). Inconsistent heroin consumption estimates derived from 6-monoacetylmorphine. Attempt to estimate from measured morphine loads and detailed prescription data. Good agreement with estimates derived from "conventional" sources. Obtained a more balanced picture of heroin consumption in the investigated area. Abstract: Background: The need to contextualise wastewater-based figures about illicit drug consumption by comparing them with other indicators has been stressed by numerous studies. The objective of the present study was to further investigate the possibility of combining wastewater data to conventional statistics to assess the reliability of the former method and obtain a more balanced picture of illicit drug consumption in the investigated area. Methods: Wastewater samples were collected between October 2013 and July 2014 in the metropolitan area of Lausanne (226, 000 inhabitants), Switzerland. Methadone, its metabolite 2-ethylidene-1, 5-dimethyl-3, 3-diphenylpyrrolidine (EDDP), the exclusive metabolite of heroin, 6-monoacetylmorphine (6-MAM), and morphine loads were used to estimate the amounts of methadone and heroin consumed. Results: Methadone consumption estimated from EDDP was in agreement with the expectations. Heroin estimates based on 6-MAM loads were inconsistent. Estimates obtained from morphine loads, combined to prescription/sales data, were in agreement with figures derived from syringe distribution data and general population surveys. Conclusions: The results obtained for methadone allowed assessing the reliability of the selected sampling strategy, supporting its ability to capture the consumption of a small cohort (i.e., 743 patients). Using morphine as marker, in combination with prescription/sales data, estimates in accordance with other indicators about heroin use were obtained. Combining different sources of data allowed strengthening the results and suggested that the different indicators (i.e., administration route, average dosage and number of consumers) contribute to depict a realistic representation of the phenomenon in the investigated area. Heroin consumption was estimated to approximately 13 g day −1 (118 g day −1 at street level).